Penyuluhan Program SBM (Save Breast Milk) Untuk Meningkatkan Kesadaran Asi Eksklusif Pada Ibu Nifas - Sherllia Sofyana (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2022)
Breast milk (ASI) is an ideal source of nutrition and the safest food for babies for 0-6 months of life. Exclusive breastfeeding can fail due to several factors, including working mothers. The SBM (Save Breast Milk) program is aimed at working mothers who have explained the importance of exclusive breastfeeding for mothers and babies as well as an explanation of good and correct breastfeeding techniques for breastfeeding mothers so that when breastfeeding, mothers and babies can feel comfortable. The aim is to increase mothers' knowledge about exclusive breastfeeding and how to store breast milk. The method is providing education through counseling for one day using a leaflet and other devices. Participants totaled 18 breastfeeding mothers. This activity was carried out in Loru Village. Based on the results of the health education provided, there is an increase in knowledge about the importance of exclusive breastfeeding and how to save breast milk for working mothers to meet their babies' nutritional needs. Working mothers are motivated to breastfeed even though they are busy working, thanks to this SBM program. The conclusion is that there is an increase in the knowledge and attitudes of breastfeeding mothers who work after being given health education about the importance of breast milk for babies and how to store breast milk to meet the nutritional needs of infants.